JURIDICAL ANALYSIS OF INFORMATION TECHNOLOGY BASED LENDING AND BORROWING IMPLEMENTATION BASED ON FINANCIAL SERVICES AUTHORITY REGULATION NUMBER 10 /POJK.05/2022 - Silitonga, Perdy; Nurwati; Sihotang, Sudiman (DE'RECHTSSTAAT, 2024)
The increasing use of information technology, especially electronically, has had an impact on the development of money lending and borrowing services that utilize technological networks, no longer only done face-to-face like conventional banks, but can be done remotely using electronic media. The aim of this research is to analyze the implementation of money lending and borrowing and find out the obstacles in the implementation of money lending and borrowing that utilize technological networks and how to overcome them. In implementing electronic lending and borrowing transactions, there is still fraud or misuse of data, even though the government has regulated electronic lending and borrowing in such a way. In its application, the method used is a notmative juridical approach by applying literature studies and statutory regulations using comparative legal methods. For this reason, the research results show that implementing information technology-based money lending and borrowing is indeed very easy, but in reality there are still many obstacles in utilizing other people's data. For this reason, it is necessary to add provisions regarding lending and borrowing in transactions, namely the obligation to carry out re-verification before disbursing funds or carrying out transactions to show that the person carrying out the transaction is the party carrying out the transaction or the same person at the time of initial registration. Specifically, the contract contained in the endowment pledge is a category of tabarru' (voluntary act) contract which in turn has a meaningful relationship with trust.